Analisis Makna Hidangan Cadhil dalam Tradisi Mudhun Lemah di Desa Lebakgowah (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the meaning of cadhil dishes in the mudhun lemah tradition in Lebakgowah Village, Lebaksiu District, Tegal Regency, Central Java. In addition, to find out the role of cadhil dishes in the socio-cultural life of the people of Lebakgowah Village. This study uses a qualitative descriptive research method that describes a phenomenon or event in its entirety with the semiotic approach of Charles Sanders Peirce. Peirce's semiotic study is used to find out the meaning of symbols (food) which are mutually agreed upon in the local community. From the results of the study, it was found that cadhil dishes in the mudhun lemah tradition in Lebakgowah Village signify gratitude to God Almighty for the blessings given to babies who are learning to walk for the first time and also set foot on the ground for the first time. The dish served is full of hope so that the child will be able to tread the life of the world with full of harmony, happiness, and fluency. In addition, cadhil dishes are also a form of non-verbal communication in society, which gives meaning to life in society with a sense of sharing. So as to create a harmonious impression that exists in the people of Lebakgowah Village. Keywords: meaning; cadhil; mudhun lemah; lebakgowah